Innovation strategies and organisational performance: The moderating role of company size among small- and medium-sized companies - Cheah, J.; Leong, S. Y.; Fernando, Yudi (Emerald Publisher, 2022)
Purpose: Not all innovative ideas or approaches commonly implemented by larger companies apply to smaller firms in all regions. Innovation that does not imply company achievements might exhaust their limited resources and cause the market to be uncompetitive. This paper aims to answer two research questions: (1) Do innovation strategies, such as process, marketing and social innovation, affect the performance of small- and medium-sized enterprises (SMEs)? (2) Does company size moderate the relationship between social and marketing innovations with SMEs' performance? Design/methodology/approach; This paper proposed three innovation strategies (i.e. social, marketing and process innovations) influencing Malaysian SMEs' performance. There were 123 valid respondents from SMEs, and the data were analysed using a structural equation modelling partial least square (SEM-PLS) technique. Findings; The research findings advocate that process innovation directly impacts SMEs' performance, not marketing innovation. Interestingly, the influence of social innovation on organisation performance is only significant when the company size becomes more prominent. Companies can provide consistent and continuous social enhancement that arouses public trust and reputation with more resources and capabilities. Also, smaller companies might concentrate their scarce resources on process innovation with instant beneficial potential instead of a sophisticated marketing strategy. Originality/value; There is limited empirical research examining how different innovation strategies, especially social innovation, affect SMEs' performance in developing countries. Furthermore, the second-generation analysis (PLS-SEM) technique provides more systematic and comprehensive results.